Ampullary stenosis and choledocholithiasis post Roux-En-Y gastric bypass: challenges of biliary access and intervention. Issue 10 (October 2020) - Wisneski, Andrew D.; Carter, Jonathan; Nakakura, Eric K.; Posselt, Andrew; Rogers, Stanley J.; Cello, John P.; Arain, Mustafa; Kirkwood, Kimberly S.; Hirose, Kenzo; Stewart, Lygia; Corvera, Carlos U.
Abstract: Background: Ampullary stenosis following Roux-en-Y gastric bypass (RYGB) is increasingly encountered. We describe cases of biliary obstruction from ampullary stenosis and choledocholithiasis to illustrate the associated diagnostic and interventional challenges with this condition. Methods: We reviewed medical records of patients with prior RYGB who underwent a biliary access procedure or surgery for non-malignant disease from January 2012–December 2018. Results: We identified 15 patients (4 male, 11 female; mean age 53.7 years) who had RYGB on average 11.7 years (range 1–32) years before diagnosis of biliary obstruction. Fourteen patients reported abdominal pain, 5 had nausea/emesis, 12 had elevated liver function tests, and 6 had ascending cholangitis. Mean common bile duct (CBD) diameter at presentation was 16.9 mm (range 4.0–25.0 mm). Operations included 3 transduodenal ampullectomies (2 with biliary bypass), 2 CBD explorations with stone extraction, 1 laparoscopic cholecystectomy alone, 1 Whipple procedure, 1 balloon enteroscopy with sphincterotomy, and 7 transgastric endoscopic retrograde cholangiopancreatography. All ampulla pathology was benign in patients who underwent resection. At follow-up (mean 15.4 months; range 0.23–44.5 months), 12/15 (80%) reported symptom resolution or improvement. Discussion: Ampullary stenosis after RYGB presents challenges for diagnostic evaluation and intervention, often requiring multi-disciplinary expertise. The underlying pathology remains to be elucidated.